Labor Productivity in the Economy of the Russian Federation: Analysis - Chernopyatov, Aleksandr M. (Opción, 2019)
This article attempts to analyze the labor productivity and its role in the national economy. It contains opinions and views of different authors on labor productivity. According to them, current labor productivity in various Russian government and private agencies is lower than in the G7 countries. This article is especially relevant in the light of the current climate of economy and the freedom of speech, which not always come in hand with fairness and deliberateness. Research novelty is that it illustrates the actual labor productivity in comparison with other proposed data.